A Quantitative Method for Intraoperative Evaluation of Distal Fibular Malrotation - Huang, Hui; Li, Zihua; Xiao, Fajiao; Xia, Jiang; Li, Bing; Yu, Tao; Zhao, Youguang; Zhou, Haichao; He, Wenbao; Li, Zhendong; Yang, Yunfeng (Frontiers in Surgery, 2022)
Background: Due to the low sensitivity of commonly used radiographic parameters for evaluation of rotational malreduction of the distal fibula under intraoperative fluoroscopy, a quantitative method is needed to make up for this defect. Methods: 96 sets of computed tomography (CT) images of normal ankle were imported into MIMICS to reconstruct 3D models. The fibula models were rotated along the longitudinal axis from 30 degrees of external rotation to 30 degrees of internal rotation. Virtual X-ray function in MIMICS was used to obtain radiographic images in mortise view. A line was drawn through the tip of the medial malleolus and parallel to the distal tibial plafond, and the distances from the medial edge of the fibula to the lateral malleolar fossa cortex and from the medial edge of the fibula to the lateral edge of the fibula were measured on this line, the ratio of them was calculated and marked as ratio α. Results: The mean ratio α for normal ankle is 0.49 ± 0.06 while the 95% confidence interval (CI) is 0.48 - 0.50. The ratio α decreases when the fibula is externally rotated and increases when the fibula is internally rotated. The effects of different gender or different types on each group of data were compared, the p values were all greater than 0.05. Conclusions: This is a new method to quantitatively evaluate rotational malreduction of the distal fibula during operation. The ratio α can correspond to the rotation angle of fibula. The larger the ratio α, the more internal rotation of the fibula will be. Contrarily, the smaller the ratio α, the more external rotation of the fibula will appear. Making the ratio α close to 0.5 may be an intuitive approach that can be used intraoperatively.